Concurrent control in the execution of public works - Gómez Guillén, Vladimir Alexis (2024)
Objective. The study seeks to describe the application of concurrent control in the execution of public works. Methods. A review of the scientific literature was considered to understand in the current the implications of concurrent control in the execution of public works, reflecting on the effect that this has, for improvement purposes through the timely application of preventive and corrective actions. Results. It was evident that concurrent control allows development optimal for the compliance of the public finality in the execution of works. Conclusions. Concurrent control is a mechanism established by the Comptroller General of the Republic (CGR) to order to manage the inclusion of preventive actions and corrective actions. Per it, these actions it's should carry out more frequently, so that public works are executed optimally, thus avoiding the presence of adverse situations.